USA - Walker, Benedict (Lonely Planet guidebooks., 2018)
Lonely Planet USA is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Gaze into the mile-deep chasm of the Grand Canyon, tap into the pulse of iconic cities like New York, or let sultry southern music and food stir your soul; all with your trusted travel companion. Get to the heart of the USA and begin your journey now!